A comparative study of clinical management strategies for vaginal discharge in family planning and genitourinary medicine settings. Issue 1 (1st January 2005) - Melville, Catriona; Nandwani, Rak; Bigrigg, Alison; McMahon, Alex D
Abstract : Objective: To compare strategies for management of women with vaginal discharge in genitourinary medicine (GUM) and family planning (FP) settings. Methods: The setting was a centre housing both FP and GUM departments within a primary care trust in Scotland. The study participants were 200 women presenting with vaginal discharge. A randomised, controlled, crossover design was employed. Strategies typical of FP and GUM were performed on every participant in a randomised sequence. Day 1 diagnoses were made by the FP strategy (history and examination) and the GUM strategy (nearpatient microscopy added). Day 7 results were obtained from final analysis of all specimens. Days 1 and 7 results were compared with the reference standard provided by all the test results. The main outcome measures were incorrect diagnoses on Days 1 and 7. Results: On Day 1 the FP strategy resulted in significantly more incorrect diagnoses than the GUM strategy when compared with the reference standard (73 vs 32; p <0.001). On Day 7 the GUM strategy resulted in significantly more incorrect diagnoses than the FP strategy when compared with the reference standard (32 vs 17; p = 0.019). Conclusions: Vaginal discharge can be managed effectively in community settings such as FP and primary care. The addition of near-patient microscopy produces a more accurate immediate diagnosis. The addition of a high vaginal swab for culture produces a more accurate final diagnosis. The costs of on-site microscopy must be considered.